Improving Grain Legume Yields in Gurué District, Mozambique Using Local Evate Rock Phosphate - António Rocha; Ricardo Maria; Rogério Rafael; Job Fugice; Upendra Singh; Unasse Saide Uaite; Kim Falinski; Russell Yost (Research Advances and Challenges in Agricultural Sciences Vol. 4, 2024)
Acid, infertile reddish-brown soils characterize large amounts of central Mozambique. Few of these soils are in food production representing a missed opportunity for agricultural productivity and a missed alternative to improve the food security of the country. These soils are mainly depleted of macronutrients such as N, P and K. Low levels of soil nutrients such as calcium, phosphorus, and potassium limit crop growth. Therefore, while N can be obtained from the air by biological nitrogen fixation (BNF) and organic sources, P and K as well others (Ca and Mg) must be provided from rocks and minerals. Local agricultural amendments for acid, infertile soils such as limestone and rock phosphate exist but are unexploited. An experiment was conducted to assess the feasibility of using local Evate rock phosphate ( 40.7% total P2O5) as a corrective to supply phosphorus. The rock phosphate was applied at rates of 20, 40, 80 and 160 kg total P ha-1. For a comparison, triple super phosphate was also added at four P levels ( 0, 10, 20 and 40 kg P ha-1). A long growth cycle crop of pigeon pea (Cajanus cajan L., Mill sp. variety “ICAEP00020”) with a growth cycle of 190 days was used to assess effectiveness of the local rock phosphate. A pigeon pea grain yield of 1000 kg grain ha-1 was possible with an application of 80 kg ha-1 of total P added as Evate rock phosphate. By comparison 20 kg P ha-1 as TSP was needed to reach a maximum yield of pigeon pea grain. This ratio suggests that Evate rock phosphate was 25% as effective as TSP on a total P basis. This research suggests that the Evate rock phosphate can be an effective amendment that can enable or enhance food grain production on the acid, infertile upland soils of Central Mozambique. Whether for direct application for acid-tolerant crops on acid soils or processed into soluble fertilizer phosphate, the existence of such a valuable resource provides a great opportunity for improved local food crop production.